Environmental management plan (EMP): Performance indicators for road and highway construction - Nurol Huda, Dahalan; Rahimi, A. Rahman; Saffuan, Wan Ahmad (AIP Publishing, 2022)
Road and highway construction (RHC) projects generally require a longer period and involve extensive excavation and earthworks. Due to the numerous environmental impacts caused by RHC projects, all parties should closely monitor these projects to identify any environmental changes. Hence, this paper aims to identify performance indicators for assessing Environmental Management Plan (EMP) of RHC projects. To achieve that aim, semi-structured interview data with Environmental Auditors and Environmental Officers were collected and then analysed using the thematic analysis technique. The interview covers the indicators and common issues raised during the construction phase. From the analysis of the interview data, eight performance indicators for assessing EMP of RHC projects were identified: irregular floods, discharge appears, overflowed silt trap, slope erosion/failure, visibility of dust, excessive noise, untypical flora and fauna, and increased accidents. Also, these indicators can be categorised into three groups: physical, biological, and socioeconomic. These findings can help novices and the public assess the EMP performance of RHC projects. Furthermore, public participation in regulating EMP can benefit both the construction industry and the authorities.